PENGARUH LIKUIDITAS, PROFITABILITAS, ACTIVITY RATIO, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Kosasih, Denisa; Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research’s purpose is to analyze the impact of liquidity, profitability, activity ratios and leverage on the financial distress (empirical study on energy and industrial sector listed on the Indonesia Stock Exchange period 2017-2021). Purposive sampling was used in this study to collect data. This study's sample included 13 companies over a five-year period. Multiple regression analysis is used in data processing techniques supported by the Eviews 12 program and Microsoft Excel. The results show that profitability and activity ratio have a positive and significant effect on financial distress in energy and industrial sector companies listed on IDX from 2017 to 2021, while liquidity and leverage have no effect on financial distress in energy and industrial sector companies listed on IDX from 2017 to 2021. The study’s implication is that the company must manage the use of asset efficiently in order to earn profits and avoid financial distress.